2011
DOI: 10.1007/s12369-010-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Age and Gender Based on Features of Human Motion Using AdaBoost Algorithms

Abstract: Automated human identification by their walking behavior is a challenge attracting much interest among machine vision researchers. However, practical systems for such identification remain to be developed. In this study, a machine learning approach to understand human behavior based on motion imagery was proposed as the basis for developing pedestrian safety information systems. At the front end, image and video processing was performed to separate foreground from background images. Shape-width was then analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Oskuie and Faez [67] extracted Zernike moments from Radon-transformed Mean Gait Energy Image [68]. Frequency-domain features obtained from the silhouette using Discrete Fourier Transform (DFT) [47] and wavelet decomposition on the silhouette contour width [69] have been used. Instead of extracting the silhouette, DCT coefficients was obtained from the image to train embedded hidden Markov models [70].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Oskuie and Faez [67] extracted Zernike moments from Radon-transformed Mean Gait Energy Image [68]. Frequency-domain features obtained from the silhouette using Discrete Fourier Transform (DFT) [47] and wavelet decomposition on the silhouette contour width [69] have been used. Instead of extracting the silhouette, DCT coefficients was obtained from the image to train embedded hidden Markov models [70].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Several studies provide valuable information, particularly for human psychology understanding and for human-machine interaction applications. Literature on the ability of human to recognize individuals from motion is abundant, in particular, it has been shown that one can recognize a known person or even him/herself accurately from gait data: arm swing, back posture for example are key features [6][7][8][9][10][11][12][13]. Most of the gait studies make use of parameters such as the stance phase, the gait cycle frequency, the length of the footsteps that can be easily measured [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…where I(i,j,t) is a binary silhouette image at current frame t, and I(i,j,t-1) is a binary silhouette image at previous frame t. The model free preprocessing used in this paper by using the motion parameter per frame [22]. First, we have to get the silhouettes image.…”
Section: Free Model Basedmentioning
confidence: 99%